Some geological-geomorphological heritages of Ba Vi area - basis for building a geopark in Hanoi - Phương, Tạ Hòa; Hiệu, Nguyễn; Dương, Nguyễn Thùy; Thảo, Hoàng Thị Minh; Đông, Bùi Văn; Cúc, Nguyễn Thị Thu (Vietnam Journal of Earth Sciences, 2014)
The Ba Vi - Son Tay has been known as a famous landscape of the Hanoi capital and as a spirit land of Vietnam. Geology of the area evolves through one last billion years. Also known as an area with high biodiversity developing on a volcanic bedrock, the area has been attracted a lot of foreign and domestic tourists. This paper introduces a scientific background on natural conditions of the area in order to construct an application dossier for nomination as a geopark. The study concentrates on geodiversity, biodiversity and unique geosites such as conglomerate bed at Dinh Vua, Po Che well with agglomerate and volcanic bomb around its mouth, ancient mining galleries at Xom Quyt and Minh Quang, streams with white waterfall at Ao Vua and Khoang Xanh, large lakes at Suoi Hai and Dong Mo,… Together with plentiful of archaeological and cultural relics, the Ba Vi - Son Tay area satisfied sufficient criteria to construct an application dossier for nomination as a geopark, which will motivate development of Hanoi tourism. Success of the project will also contribute to protect the geosites and the environment